Pengaruh Politik Hukum Kolonial Belanda Terhadap Perkembangan Hukum Ekonomi Syariah - Rezki Akbar Norrahman; Ahmadi Hasan; Jalaluddin Jalaluddin; Mariani Mariani (JOURNAL OF ISLAMIC AND LAW STUDIES, 2023)
Abstract: The influence of Dutch colonial legal politics on the development of Islamic economic law had a significant impact in the historical context of Indonesia. During the Dutch colonial period, the dominant legal system implemented was Western law, which was not in line with the principles of Sharia law. Dutch colonial legal politics had three aspects that influenced the development of Islamic economic law. First, the comprehensive adoption of Western law, including in the field of economic law. Second, unequal treatment towards local customary law and legal systems, including the existing Sharia economic system prior to the arrival of the Dutch. Third, restrictions on local legal autonomy and the use of colonial law that favored Dutch interests. However, Sharia economic law was not completely eradicated during the Dutch colonial era, and some Sharia financial practices and institutions managed to survive, albeit on a limited scale. The influence of Dutch colonialism also could not eliminate the awareness and need for Islamic economic law among the Muslim community in Indonesia.Â Abstrak: Pengaruh politik hukum kolonial Belanda terhadap pengembangan hukum ekonomi Syariah memiliki dampak yang signifikan dalam konteks sejarah Indonesia. Pada masa kolonial Belanda, sistem hukum yang diterapkan secara dominan adalah hukum barat yang tidak sejalan dengan prinsip-prinsip hukum Syariah. Politik hukum kolonial Belanda memiliki tiga aspek yang mempengaruhi pengembangan hukum ekonomi Syariah. Pertama diadopsi hukum barat secara menyeluruh, termasuk dalam bidang hukum ekonomi. Kedua perlakuan tidak setara terhadap hukum dan sistem hukum adat lokal, termasuk sistem ekonomi Syariah yang sudah ada sebelum kedatangan Belanda. Ketiga pembatasan terhadap otonomi hukum lokal dan penggunaan hukum kolonial yang lebih menguntungkan kepentingan Belanda Akan tetapi tidak sepenuhnya terhapusnya hukum ekonomi Syariah di masa kolonial Belanda dan beberapa praktik dan lembaga keuangan Syariah masih bertahan meskipun dalam skala yang terbatas. Pengaruh kolonial Belanda juga tidak dapat menghilangkan kesadaran dan kebutuhan akan hukum ekonomi Syariah di kalangan masyarakat Muslim Indonesia.